Cleavage nature and surface appearances of wulfenite by first-principles calculations and experimental measurement - Baoxu Song; Dongping Tao; Peilun Li; Xiaodong Wang; Jincheng Ran (Results in Physics, 2020)
Natural wulfenite is lead molybdate (PbMoO4), which has extensive and vital economical values based on its rarity and molybdenum extraction. Through the density functional theory calculation, the electronic structure and bond population were first investigated, and the predominantly exposed surfaces were predicted. Based on the calculations, the {1 1 2} and {0 0 1} surfaces are expected to be the most common cleavage surfaces due to their lower surface energies, smaller broken bond densities, and larger interlayer spacings than other surfaces; and the results are consistent with the X-ray diffraction (XRD) observations. Moreover, the {1 1 2} and {0 0 1} cleavage surfaces were intuitively observed by atomic force microscopy (AFM), and {1 1 2} cleavage surfaces are rather smooth and flat, while the {0 0 1} cleavage surface have separated terrace, indicating that the cleavages occur more easily along {1 1 2} surfaces than along {0 0 1} surfaces. The above conclusions in this paper have important theoretical significance and guidance on in-deep understanding of the wulfenite leaching and flotation mechanisms.